The Effect of Using Monosodium Glutamate (MSG) in Food On Body Health - Reko Alya Gita Prawadya; Satrio Budi Utomo; Saryono Saryono (International Journal of Biomedical Nursing Review, 2023)
Background: Monosodium glutamate (MSG) is a food additive that is often used as a flavor and aroma enhancer in processed foods. Several studies have shown that consuming high amounts of MSG can affect body health and cause symptoms such as headaches, nausea, vomiting, excessive sweating, and high blood pressure in some sensitive people. In addition, several studies have also found that MSG consumption can increase the risk of obesity, type 2 diabetes, cardiovascular disease, and metabolic disorders. Objective: This systematic review aims to determine the effect of using monosodium glutamate (MSG) in food on the health of the body so that readers can make wise decisions in choosing foods that are healthy and safe for consumption. Method: Using the PRISMA method, search for journals in electronic databases published on Google Scholar, PubMed, and ScienceDirect that were published from 2013 to 2023. These articles were then extracted, taking into account the titles and abstracts to determine their suitability for the topics discussed. Results: Of the 8 selected articles, it shows that monosodium glutamate used in food has a bad influence on body health. Glutamic acid contained in MSG can increase body weight and damage liver and kidney function if consumed above the safe limit, which is 30 mg/kg/day of body weight. When MSG is used every day, it can cause symptoms of headache (85.8 mg/kg), increased insulin (> 143 mg/kg), and increased blood pressure (150 mg/kg). Conclusion: Monosodium glutamate (MSG) is an additive commonly used as a flavor enhancer in food. Consuming excessive MSG can increase the risk of various health problems, but the use of MSG in moderate and controlled amounts does not have a negative impact on the health of the body.